Study on the pathogenicity, immunogenicity, endogenous development and drug sensitivity of Eimeria kongi - Fang, Sufang; Shi, Yubo; Wang, Peng; Guan, Chen; Gu, Xiaolong; Guan, Lihui; Cui, Ping; Suo, Xun (Frontiers in Veterinary Science, 2023)
Following the discovery of Eimeria kongi, we investigated the pathogenicity, immunogenicity, endogenous development and drug sensitivity of this coccidian. Coccidia-free rabbits were inoculated with 1×102 to 5×104 sporulated oocysts of Eimeria kongi before challenge 14 days post inoculation. Eimeria kongi was moderately pathogenic and induced good immunity against re-infection. All inoculated doses results in reduced food intake and body weight gain, and an inoculation oocyst dose of 1×103 or higher caused various degrees of diarrhea. Except for one death of the highest dose group, all rabbits recovered 12 days post inoculation. An inoculation dose of 1×103 or 1×104 oocysts conferred the most effective protection from re-infection, which reduced oocyst output by approximately 99% and maintained body weight gain. Four generations of schizogony were observed, and the endogenous development mainly occurred in the jejunum and ileum of rabbits. Eimeria kongi was most sensitive to sulfachloropyrazine sodium, followed by decoquinate; it is resistant to diclazuril. Both decoquinate and sulfachloropyrazine sodium may be effective in the control of Eimeria kongi infection.